Citizens and soldiers : the dilemmas of military service - Cohen, Eliot A. (Cornell studies in security affairs., 2019)
Why has the United States, unlike every other 20th-century world power, failed to settle on a durable system of military service? In this lucid book, Eliot Cohen studies the enduring problems of America's methods of raising an army.